Reflections on historical pandemics and Mahidol University’s research on the treatment and prevention of influenza outbreaks - Pukrittayakamee, S; Poovorawan, K; Peto, TJ; Phumratanaprapin, W (Royal Society of Thailand, 2020)
Epidemics of infectious diseases have threatened humans throughout our history. Devastating plagues are described in records from classical Greece and Rome and across the ancient world. Many epidemic diseases that now affect humans began from infections that originated in animals. In the 21st century, we live in a world in which there have been dynamic changes to the global ecology and expanded international travel, which has resulted in increased contact between humans, and between humans and animals. The result is that the emergence and spread of new contagious infections from animal reservoirs and between human populations has become both more probable and, in some aspects, also more difficult to contain. Pandemics in the 21st century are anticipated to have chiefly viral causes, such as influenza, corona and arboviruses. Unlike bacteria, virus proteins are readily altered through antigenic drift and shift. In the case of the latter, a new viral infection may enter an entirely susceptible human population who have never been exposed before and have no effective host immunity. Moreover, existing treatments may prove ineffective, and new vaccines will need to be developed. Another reason why animal-to-human, or “zoonotic” viruses are of great concern is that these can often be efficiently transmitted through droplets, from animal to person, and also from human to human. Unlike most viruses, the influenza virus exists as a seasonal epidemic and when a new influenza virus strain appears there is the potential for it to also from human to human. Unlike most viruses, the influenza virus exists as a seasonal epidemic and when a new influenza virus strain appears there is the potential for it to spread rapidly and widely across international borders and around the world, that is, to become a pandemic. In this short review we reflect on a several key aspects of past pandemics, with a focus on the influenza infections. We then present an overview of recent studies conducted by the Faculty of Tropical Medicine, Mahidol University to improve the treatment and prevention of influenza.